Dexmedetomidine-Tiletamine-Zolazepam Followed by Inhalant Anesthesia in Spectacled Bears (Tremarctos ornatus) - Garofalo, Natache Arouca; Justo, André Augusto; Araújo, Stephanie Cristine Miyamoto; de Lima, Mayara Travalini; Teixeira, Carlos Roberto; Neto, Francisco José Teixeira (Acta Scientiae Veterinariae, 2021)
Background: The spectacled bear (Tremarctos ornatus) is the only bear species inhabiting South America and is classified as vulnerable according to the International Union for Conservation of Nature (IUCN) Red List. Among the few publications on the use of general anesthesia and advanced monitoring of ursids in veterinary hospital settings, little is described regarding chemical restraint, general anesthesia and monitoring of spectacled bears. This case series describes the use of a dexmedetomidine-tiletamine-zolazepam chemical restraint combination and its effects on cardiorespiratory variables and arterial blood gases observed in two spectacled bears submitted to isoflurane anesthesia for imaging and/or surgical procedures. Cases: Two female, one adult and one senile, all-term captive spectacled bears were referred to the Veterinary Medical Teaching Hospital at the Universidade Estadual Paulista - Unesp, Botucatu campus, both with a presumable history of recent trauma. After immobilization with an intramuscular (IM) administration of tiletamine-zolazepam (3.8 - 4.3 mg/kg) and dexmedetomidine (6.4 - 7.6 µg/kg), anesthesia induction was achieved by means of intravenous (IV) propofol (1 - 2 mg/kg). The patients then underwent isoflurane inhalant anesthesia and were submitted to intermittent positive-pressure ventilation through the remainder of the procedures. Initial settings of inspiratory flow rate were adjusted to obtain Ppeak of 10 cmH2O and tidal volumes (Vt) of 10 mL/kg, as well as respiratory rates (ƒR)and inspiration-to-expiration (I:E) ratio of 10 breaths/min and 1:2, respectively, and were then adjusted throughout anesthesia to maintain normocapnia (end-tidal carbon dioxide concentrations between35 and 45 mmHg). One of the individuals was chemically restrained (6.4 mg/kg of tiletamine-zolazepam and 7.7 µg/kg of dexmedetomidine) on a second anesthetic event for imaging procedures. Arterial blood gas analysis were performed with the subjects breathing room air and oxygen-enriched air. Both animals exhibited severe hypoxemia (partial pressure of oxygen [PaO2] < 60 mmHg) while breathing room air (inspired oxygen fraction [FiO2] ≅ 0.21). An impaired blood oxygenation (PaO2/FiO2 < 400) was still observed despite mechanical ventilation and the provision of 1.0 FiO2. Alveolar recruitment maneuvers (3 sequential mechanical sights with peak airway pressure at 20 - 30 cmH2O during 15 - 30 s each) were then performed, which resulted in improved PaO2/FiO2 ratios. All other blood gas, electrolytes and acid-base variables did not appear to be importantly altered by chemical restraint and general anesthesia. Discussion: Dexmedetomidine-tiletamine-zolazepam resulted in reliable chemical restraints and is a feasible option for immobilizing spectacled bears, though severe hypoxemia may proceed. Hypoxemia is the most commonly described complication in bear anesthesia, and was also evidenced in the current report. However, low PaO2/FiO2 ratios tend to be accompanied by hypercapnia and therefore counteracted by oxygen supplementation in bears, which was not observed in the present report. In fact, blood oxygenation only reached regular values after alveolar recruitment maneuvers, which is compatible to an atelectasis-related hypoxemia. Therefore, either inhalant anesthesia or field chemical restraint should be accompanied by advanced monitoring (cardiorespiratory variables and blood gas analysis) in until further studies address the management of hypoxemia in spectacled bear. since Advanced monitoring was of major importance for a safe outcome and an uneventful recovery in this species. Keywords: balanced anesthesia, dexmedetomidine, general anesthesia, spectacled bear, Tremarctos ornatus, wildlife.